Inducing hypertension in Myh11R247C/R247C mice triggers aortic dissections with increased focal adhesion kinase signaling - Kwartler, Callie S.; Wang, Shanzhi; Zhou, Zhen; Guan, Pujun; Yu, Yang; Duan, Xue-Yan; Zhang, Theodore; Chen, Jiyuan; Davis, Elaine C.; Milewicz, Dianna M. (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveWe sought to determine if hypertension in combination with a “variant of uncertain significance” that disrupts protein function, MYH11 p.Arg247Cys, would induce aortic dissections in a mouse model.Approach and resultsAdministration of L-NAME via drinking water and a high salt diet increased blood pressure in WT and Myh11R247C/R247C mice and triggered type A dissections with cardiac tamponade in 20% of the Myh11R247C/R247C mice. Myh11R247C/R247C aortas have aberrant smooth muscle contractile unit-elastin connections by transmission electron microscopy, along with increased focal adhesion signaling at baseline, which further increases with hypertension.ConclusionGene-environment interactions trigger aortic dissections in Myh11R247C/R247C mice.